The bradykinin-forming cascade in anaphylaxis and ACE-inhibitor induced angioedema/airway obstruction - Ghebrehiwet, Berhane; Joseph, Kusumam; Kaplan, Allen P. (Frontiers in Allergy, 2024)
Anaphylaxis is a potentially life-threatening multi-system allergic reaction to a biological trigger resulting in the release of potent inflammatory mediators from mast cells and basophils and causing symptoms in at least two organ systems that generally include skin, lungs, heart, or gastrointestinal tract in any combination. One exception is profound hypotension as an isolated symptom. There are two types of triggers of anaphylaxis: immunologic and non-Immunologic. Immunologic anaphylaxis is initiated when a foreign antigen directly binds to IgE expressed on mast cells or basophils and induces the release of histamine and other inflammatory substances resulting in vasodilation, vascular leakage, decreased peripheral vascular resistance, and heart muscle depression. If left untreated, death by shock (profound hypotension) or asphyxiation (airway obstruction) can occur. The non-immunologic pathway, on the other hand, can be initiated in many ways. A foreign substance can directly bind to receptors of mast cells and basophils leading to degranulation. There can be immune complex activation of the classical complement cascade with the release of anaphylatoxins C3a and C5a with subsequent recruitment of mast cells and basophils. Finally, hyperosmolar contrast agents can cause blood cell lysis, enzyme release, and complement activation, resulting in anaphylactoid (anaphylactic-like) symptoms. In this report we emphasize the recruitment of the bradykinin-forming cascade in mast cell dependent anaphylactic reactions as a potential mediator of severe hypotension, or airway compromise (asthma, laryngeal edema). We also consider airway obstruction due to inhibition of angiotensin converting enzyme with a diminished rate of endogenous bradykinin metabolism, leading not only to laryngeal edema, but massive tongue swelling with aspiration of secretions.